3(-4-9n)-6n=

Simple and best practice solution for 3(-4-9n)-6n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-4-9n)-6n= equation:


Simplifying
3(-4 + -9n) + -6n = 0
(-4 * 3 + -9n * 3) + -6n = 0
(-12 + -27n) + -6n = 0

Combine like terms: -27n + -6n = -33n
-12 + -33n = 0

Solving
-12 + -33n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -33n = 0 + 12

Combine like terms: -12 + 12 = 0
0 + -33n = 0 + 12
-33n = 0 + 12

Combine like terms: 0 + 12 = 12
-33n = 12

Divide each side by '-33'.
n = -0.3636363636

Simplifying
n = -0.3636363636

See similar equations:

| 84=6(2-x)-3x | | -2=-2(n-8) | | 7(-4-5p)-4=-207 | | 5x+4-7x=5+x+13 | | 29+2x=x+25 | | 8-3y=-4 | | 4x^3+x^3+9x^2=0 | | -102=-2(8-7r)-2 | | x-3(8)=-4 | | y=50x+90 | | 2x+27=x+21 | | 4(v+7)=6v+18 | | 31=7+3x | | (2x-5)(2x-5)-121=0 | | 8(1-2r)=-88 | | 18+x=x+23 | | 7-3a=-16 | | -2x+4=5+1x-13 | | 4x+y-47=0 | | 4u+36=6(u+4) | | 3x+1=4+x | | (2x)+x+(2x+5)=50 | | 3p^2-9p-1=0 | | 2b-67=-8n+5 | | -6n=27 | | (c+3)-(1-3c)=2 | | -5x-3=y | | 256-9x=0. | | -9(w+8)=-3w-36 | | (2x+7)(x^2+7x+8)= | | 4(3a-3)+4=35 | | -9+4n=27 |

Equations solver categories